cThe Impact of AI on Changes in Critical Thinking and Interest in Learning Among Students and College Students - Alfrida, Hassya Nailah (Maliki Interdisciplinary Journal, 2026)
Artificial Intelligence or commonly known as AI is a technology that is designed and can imitate human intelligence that can be accessed by all groups from students to workers, and AI can also help make it easier to solve easy and even difficult problems, in addition AI also helps in the development process for students and college students, but not always AI brings a good influence to its users, all can be seen through how the use can manage information well and correctly, but in fact at this time AI has become a platform that can bring bad influences to its users especially in the field of education and learning, which can cause a decrease in the ability of students and college students to think critically and their interest in learning, because most of them think that AI is a practical shortcut in dealing with problems in the field of education and learning, so the purpose of this journal is to find out the impact of the use of AI that can result in a decrease in critical thinking and interest in learning for students and college students and solutions so that this does not happen continuously and cause losses for students and college students in the long term, and this journal is written using a qualitative descriptive method through a literature study approach sourced from journals, articles and other credible sources that can be material in the discussion of the journal This.